The Evolution of Smart City Policy in China: A Quantitative Study Based on the Content of Policy Texts - Chongfeng Yue; Hongyan Li; Haocheng Mao; Aobo Yue (Buildings)
As China is the largest developing country and the country with the largest volume of smart city construction, the Chinese government has promulgated a series of policies to develop smart cities vigorously. Thus, the understanding of smart city policies from the perspective of policy science theory is helpful in achieving a full understanding of the development stage and evolution path of smart cities and improving the implementation of smart city policies. In this study, text content mining and quantitative empirical analysis are used to investigate the structure and function of China’s smart city policy. The results demonstrate that China’s smart city policy has largely realized the evolutionary process of the policy keynote from “taking” to “giving” and the policy subject from “single” to “pluralistic”. The organizational structure has gradually turned from “multidisciplinary” to “cooperative governance”. The analysis results indicate that the policy guidance for smart cities should focus on the positive interaction between social needs and urban development regulations. It is also important to enhance citizen participation and redefine the role of the government in the development of smart cities.